The proposal of law about "doctor-assisted voluntary death". Critical issues on the document under discussion in the Senate - Sartea, Claudio (Medicina e Morale, 2022)
The essay analyzes the proposal of law about "doctor-assisted voluntary death" that the Italian Senate is discussing in recent weeks after the approbal of the Italian Chamber of Deputies, and higlights its main critical issues from a bio-juridical perspective